Haematoma block or Bier's block for Colles' fracture reduction in the accident and emergency department–which is best?. Issue 6 (November 1997) - Kendall, J M; Allen, P; Younge, P; Meek, S M; McCabe, S E
Abstract : OBJECTIVE: To offer clear guidance on the anaesthetic management of Colles' fractures in the accident and emergency (A&E) department in the light of the conflict between existing reports and current trends, and to address the issue of alkalinisation of haematoma blocks. METHODS: This was a two centre, prospective, randomised clinical trial with consecutive recruitment of adult patients with Colles' fractures requiring manipulation to receive either Bier's block or haematoma block. There was subsequent blinded randomisation to alkalinised or non-alkalinised haematoma block. RESULTS: 72 patients were recruited into the Bier's block group, and 70 into the haematoma block group. Bier's block was less painful to give than the haematoma block (median pain score 2.8 v 5.3; P << 0.001), and fracture manipulation was also less painful in the Bier's block group (median pain score 1.5 v 3.0; P < 0.01). There was no significant difference in overall A&E transit time between the two groups. There was better initial radiological outcome in terms of dorsal angulation in the Bier's block group (-3.6 degrees v 2.1 degrees; P = 0.003). More remanipulations were required in the haematoma block group (17/70 v 4/72; P = 0.003). There was a trend towards decreased pain on administration of the alkalinised haematoma block when compared with non-alkalinised haematoma block, but this did not reach significance. There was no difference in pain score on fracture manipulation. There were no complications in either group. CONCLUSIONS: Bier's block is superior to haematoma block in terms of efficacy, radiological result, and remanipulation rate; transit times are equal, both procedures are practical in the A&E environment, and there were no complications. Bier's block is the anaesthetic management of choice for Colles' fractures requiring manipulation within the A&E department.